HUBUNGAN ANTARA AKTIVITAS ANAK USIA DINI PADA PENGGUNAAN MEDIA PEMBELAJARAN MENJAHIT DENGAN KEMAMPUAN MOTORIK HALUS (Penelitian Kuantitatif di Kelompok A RA Al-Mukhlisin Lengkong Kabupaten Bandung) - Mira Miranti Suherman (JIP: Jurnal Ilmu Pendidikan, 2026)
This research is motivated by the gap between the high activity of early childhood children in the use of sewing learning media and the low fine motor skills of children in Group A RA Al-Mukhlisin Lengkong, Bandung Regency. This can be seen from the children's response when the children's activities in the use of sewing learning media are able to follow until completion. On the other hand, children's fine motor skills are still not developed as seen from the children's inability to button clothes, tie shoelaces, and trace shapes. This study aims to determine how the activities of early childhood children in the use of sewing learning media, fine motor skills, and the relationship between the two. Fine motor skills are influenced by several factors, one of which is the child's activity in the use of sewing learning media. Children's activities in the use of sewing learning media can optimize eye-hand coordination, wrist flexibility, and strength and flexibility of the fingers. The research methodology used is a quantitative approach with a correlation method. The subjects of this study were 37 children in Group A RA Al-Mukhlisin Lengkong, Bandung Regency. This study used a saturated sampling technique, which means that all populations were sampled. The data collection technique of this research uses observation and documentation. The results of data analysis show that the activities of early childhood in the use of sewing learning media obtained an average value of 60. This figure is in the range of 60-69 which is interpreted as sufficient. While fine motor skills obtained an average value of 77. This figure is in the range of 70-79 which is interpreted as good. Furthermore, the relationship between the activities of early childhood in the use of sewing learning media with fine motor skills obtained a correlation coefficient of 0.412. The results of the significance test obtained t count = 2.677 and t table at a significance of 5% with db = 35 of 2.030. Because t count = 2.677> t table = 2.030, then Ho (null hypothesis) is rejected and Ha (alternative hypothesis) is accepted. In other words, the activities of early childhood in the use of sewing learning media have a positive and significant relationship with fine motor skills. Furthermore, children's activities using sewing learning media contributed 16.97% to fine motor skills in Group A of RA Al-Mukhlisin Lengkong, Bandung Regency. The remaining 83.03% was influenced by other factors not examined in this study